2000
DOI: 10.1046/j.1460-9568.2000.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral blockade of NMDA receptors in anterior thalamus by dizocilpine (MK‐801) injures pyramidal neurons in rat retrosplenial cortex

Abstract: Non-competitive N-methyl-D-aspartate (NMDA) receptor antagonists, ketamine, phencyclidine (PCP) and dizocilpine (MK-801), produce psychosis in people. In rodents they produce cytoplasmic vacuoles in injured retrosplenial cortical neurons that express HSP70 heat shock protein. This study examined possible circuits and receptors that mediate this neuronal injury. Bilateral, but not unilateral, injection of dizocilpine (5, 10, 15, 20 microg/microL per side) into the anterior thalamus induced HSP70 protein in pyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 90 publications
(121 reference statements)
2
42
0
Order By: Relevance
“…In accordance with these findings, it has been shown that the local application of PCP into the hippocampus increases locomotion and the firing of pyramidal neurons of the mPFC in freely moving rats (Jodo et al, 2005). Furthermore, Sharp and coworkers have described that the blockade of NMDA receptors in the anterior thalamus by MK-801 resulted in injury of cortical pyramidal neurons measured by an increased synthesis of heat-shock protein 70 (HSP-70) in limbic cortex (Tomitaka et al, 2000;Sharp et al, 2001). Thus, all these findings suggest that NMDA receptor antagonists would attenuate the tonic activation of inhibitory (GABA) neurons (possibly, though not exclusively, in the hippocampus and/or the thalamus), which would result in a disinhibition of glutamatergic input to the mPFC (Olney and Farber, 1995;Moghaddam et al, 1997;Krystal et al, 2003).…”
Section: Discussionmentioning
confidence: 73%
“…In accordance with these findings, it has been shown that the local application of PCP into the hippocampus increases locomotion and the firing of pyramidal neurons of the mPFC in freely moving rats (Jodo et al, 2005). Furthermore, Sharp and coworkers have described that the blockade of NMDA receptors in the anterior thalamus by MK-801 resulted in injury of cortical pyramidal neurons measured by an increased synthesis of heat-shock protein 70 (HSP-70) in limbic cortex (Tomitaka et al, 2000;Sharp et al, 2001). Thus, all these findings suggest that NMDA receptor antagonists would attenuate the tonic activation of inhibitory (GABA) neurons (possibly, though not exclusively, in the hippocampus and/or the thalamus), which would result in a disinhibition of glutamatergic input to the mPFC (Olney and Farber, 1995;Moghaddam et al, 1997;Krystal et al, 2003).…”
Section: Discussionmentioning
confidence: 73%
“…Animal studies using the MK-801 injury model used here have identified regions, circuits and receptors that interact to produce injury in limbic cortex via activation of thalamus and basal forebrain (Tomitaka et al, 2000b;Sharp et al, 2001;Farber et al, 2002Farber et al, , 2003. Although the current study does not address mechanisms and sites of action of the atypical antipsychotic drugs, it is likely the atypical antipsychotics protect retrosplenial cortex by blocking dopamine D2 and other receptors associated with thalamic, midbrain, and basal forebrain projections to limbic cortex (Farber et al, 2003;Sharp et al, 2001).…”
Section: Discussionmentioning
confidence: 93%
“…Cell counts were performed as previously described (Tomitaka et al, 2000b). Counts were performed at  100 magnification within a 0.1 mm 2 area centered over layer III in the retrosplenial cortices using a microcomputer-imaging device (MCID, London, Canada).…”
Section: Cell Counting and Statisticsmentioning
confidence: 99%
“…This hyper-excitation has been related to an increase in thalamo-cortical glutamatergic excitation of downstream cortical regions such as the anterior cingulate and retrosplenial cortices (Tomitaka et al, 2000;Holcomb et al, 2005). PET scan studies have shown that schizophrenic subjects respond to ketamine with higher hypermetabolism than normal subjects.…”
Section: Introductionmentioning
confidence: 99%